PEMANFAATAN POTENSI ALAM KOTA REMPAH MELALUI PENGOLAHAN MINYAK ATSIRI DAGING BUAH PALA (Myristica fragrans) DI KELURAHAN TANAH TINGGI BARAT KOTA TERNATE - Amran Nur; Eri Marwati; Bambang Tjiroso (Jurnal Abdi Insani, 2023)
Ternate City is situated at the base of the Gamalama volcano on Ternate Island in North Maluku Province. It is renowned for its production of spices. North Maluku is commonly referred to as the Spice City or The Spicy Island. The nutmeg agribusiness in North Maluku is highly viable from both a financial and economic standpoint, as it possesses distinct comparative and competitive advantages. This Community Service Activity (PKM) is an initiative by the implementing team from Khairun University to convey knowledge about the health advantages of nutmeg flesh and the procedure of extracting essential oils from it. Goal: To enhance public awareness of the health advantages of nutmeg pulp, improve community proficiency in the production and processing of nutmeg flesh into essential oil, and foster the growth of nutmeg commodity enterprises as a primary ingredient for traditional medicine. Method: The activity was conducted utilizing a collaborative strategy, namely by reaching out to community groups in the Tanah Tinggi Barat (Tantibar) Subdistrict. The outreach session focused on elucidating the health advantages of nutmeg pulp, essential oils, and their respective manufacturing processes. This workshop will provide instruction and hands-on experience in the production of nutmeg essential oil. Outcome: The execution of this outreach and training initiative proceeded seamlessly, with the community displaying a high level of enthusiasm and active involvement. Prior to the activities in Tanah Tinggi Barat sub-district, the community was informed about the advantages of nutmeg essential oil through outreach efforts. Subsequently, once the community comprehends the advantages of essential oils, they proceed to engage in the process of producing essential oils by utilizing discarded nutmeg meat from the gardens of local inhabitants. Transforming nutmeg into essential oil. Summary; . The outcomes of this exercise expanded the understanding of the residents of Tantibar Village regarding the advantageous properties of nutmeg essential oil, particularly for health purposes.